Western Legal Hegemony over Customary Law: A Critical Legal Studies (CLS) Perspective - Rachmadi Usman (Journal of Adat Recht, 2025)
This study examines Western legal hegemony over customary law in Indonesia from the perspective of Critical Legal Studies. Using a normative juridical method, the research analyzes how epistemic, institutional, and ideological mechanisms shape legal hierarchies that elevate Western state law while subordinating customary law. The findings reveal that Western legal epistemology dominates the definition of law, limiting legal legitimacy to written and codified norms and marginalizing living customary systems. Institutional frameworks reinforce this hierarchy through the monopoly of state courts, codification requirements, and statutory land governance that undermine indigenous jurisdiction. Ideological hegemony further constructs Western law as modern and neutral while framing customary law as inferior, leading to internalized cultural displacement. The study concludes that customary law can gain equal legal authority only through structural and epistemic reform that acknowledges indigenous legal philosophies as autonomous sources of justice